Effect of Class C Pulverized Fuel Ash on Shear Strength of Silty Sand Soil Type - Siti Khadijah Binti Saiful Bahari, Siti Khadijah (Universiti Teknologi Petronas, 2008)
The potential usage of PFA in soil stabilization has increased significantly due to increased availability and the introduction of new environmental regulations that encourage the use of PFA in geotechnical applications when it is environmentally safe. The main objective for this project is to investigate the benefit of using PFA for soil stabilization. This study covers the basic characteristics of soil and PFA, compaction, shear strength parameters and Atterberg limit. The samples were subjected to unconfined compression tested immediately as compacted and after curing for 3 and 7days at temperature of 38°C to develop water contentstrength relationship. This soil was mixed with different percentages of PFA varying from 9% to 24% with increment of 3% by dry weight of soil. Soil samples were collected from oil-palm plantation at Changkat Cermin while PFA were collected from TNB Manjong. The soil sample was predominantly quartz while the PFA is classified as Class C PFA. The mixtures between soil and PFA had increased the compaction and shear strength behavior. The optimum dry density was achieved when PFA content was 12%. Shear strength of the soil-PFA mixtures were increased 50% during immediate test and the greatest shear strength acquired was during 7 days of curing with PFA content of 21%. During the experiments all samples failed with visible shear failure with angle of 60-65° and all samples became more brittle after curing. The particles sizes of soil-PFA mixtures became more solid and contain lesser air voids compared to the untreated soil. The bonding between these materials indicated chemical reactions had occurred in these materials to form cementation product. From the experiments conducted, it can be concluded that the addition of Class C PFA has improved the engineering properties of soft soil significantly